Tumor Size Predicts Muscle-invasive and Non-organ-confined Disease in Upper Tract Urothelial Carcinoma at Radical Nephroureterectomy - Collà Ruvolo, Claudia; Nocera, Luigi; Stolzenbach, L Franziska; Wenzel, Mike; Califano, Gianluigi; Tian, Zhe; Verze, Paolo; Shariat, Shahrokh F; Saad, Fred; Briganti, Alberto; Mirone, Vincenzo; Karakiewicz, Pierre I (European urology focus, 2022)
BACKGROUND: Pathological stage and grade of renal pelvis urothelial carcinoma (RPUC) are difficult to estimate before radical nephroureterectomy (RNU). OBJECTIVE: To examine tumor size as an independent predictor of muscle-invasive and/or non-organ-confined rates of RPUC at RNU. DESIGN, SETTING, AND PARTICIPANTS: Within the Surveillance, Epidemiology and End Results (SEER) database (2004-2016), we identified nonmetastatic RPUC at RNU. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: First, we examined stage and grade distributions. Second, two separate univariable and subsequent multivariable logistic regression models (LRMs) were fitted to test the association between tumor size and the rate of (1) muscle-invasive or higher (pT2-4N0-2) and (2) non-organ-confined (pT3-4N0-2) RPUC at RNU. RESULTS AND LIMITATIONS: Of 4657 patients, 3052 (65.5%) had pT2-4N0-2 and 2382 (51.2%) pT3-4N0-2 RPUC at RNU. The median tumor size was 3.7 cm (interquartile range 2.5-5.0). The high-grade RPUC rate ranged from 71.1% to 87.2% (p < 0.001) among SEER registries. Conversely, no differences were recorded for stage (p > 0.05) or tumor size (p = 0.1) across all registries. Rates of pT2-4N0-2 and pT3-4N0-2 RPUC increased with tumor size. Specifically, for tumor size intervals from 0.1-1.0 cm to 9.1-10.0 cm, the pT2-4N0-2 rate ranged from 45% to 83% and the pT3-4N0-2 rate ranged from 23% to 75%, respectively (both p < 0.001). In multivariable LRMs, tumor size (in 1-cm units) was an independent predictor of pT2-4N0-2 (odds ratio [OR] 1.25; p < 0.001) and pT3-4N0-2 (OR 1.30; p < 0.001) disease at RNU. CONCLUSIONS: Tumor size is a key predictor of muscle-invasive or non-organ-confined RPUC. Greater tumor size directly and virtually linearly predicts a higher rate of invasive or non-organ-confined RPUC at RNU. PATIENT SUMMARY: For patients with cancer in urinary tract cells lining the kidney, larger tumor size predicts worse stage of the disease at surgery.
Keywords: Retrospective Studies; nádory močového měchýře; lidé; Upper tract urothelial carcinoma; nádory močovodu; karcinom z přechodných buněk; Muscles; Nephroureterectomy; Radical nephroureterectomy; Kidney Neoplasms; Ureteral Neoplasms; Tumor dimension; retrospektivní studie; Humans; svaly; Tumor stage; nefroureterektomie; Surveillance, epidemiology and end results database; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; nádory ledvin